Instructional collaboration in international inclusive education contexts - Semon, Sarah R.; Lane, Danielle; Jones, Phyllis; Forlin, Chris (International perspectives on inclusive education ;, 2021)
The journey towards inclusive education and collaborative practices in different countries is complex and interdependent within each unique geopolitical landscape. Instructional Collaboration in International Inclusive Education Contexts looks at the instructional collaboration between special education and general education in international educational contexts and the role this plays in enabling inclusive education. This book provides insights into how collaborative practices are enacted in support of inclusive education in different countries around the world. Presenting a theoretical framework of instructional collaboration to provide an understanding of the commonalities, differences, and challenges of collaboration internationally. Scholars from thirteen nations each contribute towards the implementation of instructional collaborative practices and highlight how instructional collaboration is developed from teacher preparation programs, describing how this is implemented in schools to provide insight of the social and political considerations that impact on the promotion of inclusive education in the context of their country. Instructional Collaboration in International Inclusive Education Contexts is essential reading for researchers and professionals with a focus on inclusive and special education.